2017
DOI: 10.1111/1462-2920.13688
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycerol in the pathogenic lifestyle of the rice blast fungus Magnaporthe oryzae

Abstract: SummaryThe rice blast fungus Magnaporthe oryzae elaborates a specialized cell called an appressorium, which is used to breach the tough outer cuticle of a rice leaf, enabling the fungus entry to host plant cells. The appressorium generates enormous turgor by accumulating glycerol to very high concentrations within the cell. Glycerol accumulation and melanization of the appressorium cell wall collectively drive turgormediated penetration of the rice leaf. In this review, we discuss the potential metabolic sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 45 publications
0
74
0
Order By: Relevance
“…Additionally, in the appressoria of C. fructicola , a vacuole nearly filled the cell. The vacuole of appressoria as a central element of the lytic system takes up lipid droplets to generate glycerol, contributing to appressorium turgor generation (Foster et al , ). In this study, the appressorial cone pad was close to the vacuole, which could protect the appressorial vacuole from being pierced by the appressorial cone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the appressoria of C. fructicola , a vacuole nearly filled the cell. The vacuole of appressoria as a central element of the lytic system takes up lipid droplets to generate glycerol, contributing to appressorium turgor generation (Foster et al , ). In this study, the appressorial cone pad was close to the vacuole, which could protect the appressorial vacuole from being pierced by the appressorial cone.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological observations showed that appressoria of the cothr4 mutant induced by exogenously supplied threonine exhibited a reduction in turgor generation. In C. orbiculare and M. oryzae , the melanin layer in the appressorial cell wall is a semipermeable membrane that blocks the efflux of glycerol from the appressorium, leading to high turgor pressure [47, 48]. We noticed that melanization in appressoria of the cothr4 mutant induced by exogenously supplied threonine was slightly weaker than that in the wild-type (Fig 4).…”
Section: Discussionmentioning
confidence: 95%
“…62 Accordingly, several aspects of fungal cell biology that are relevant in the context of infection were addressed in the final IFoFun-2016 session that was hosted by Frank Ebel from Munich, Germany. Lauren Ryder from Exeter, UK, focused on turgor pressure modulation of the rice blast fungus Magnaporthe oryzae 63 by an osmosensing histidine kinase that supports pathogenicity but also acts as negative regulator of melanin synthesis. Holger Deising from Halle, Germany, presented data on evasion of the model pathogen Colletotrichum graminicola from plant PAMPtriggered immunity by surface modulations in biotrophic hyphae 64 and how to use host-induced silencing of essential fungal genes to improve plant health.…”
Section: Manipulating the Host -Extracellular Effectors And Host-pathogmentioning
confidence: 99%